Calcium Homeostasis in Escherichia coli: Characterization of Mutants and Genome Expression of MG1655 (Bangladesh Journal of Microbiology, 2016)
While the role of calcium ions as secondary messengers has been well described in eukaryotic cells, little is known about calcium homeostasis in bacteria at the physiological and molecular levels. Genetic and genomic approaches were used to address calcium regulation and to identify genes (cal) involved in calcium homeostasis. Transposon mutagenesis of Escherichia coli generated several calcium-sensitive mutants that fell into three categories: (i) Ca2+-sensitive chemotaxis mutants, (ii) Ca2+-sensitive cell division mutants, and (iii) Ca2+-sensitive mutants that showed no defects in cell division or chemotaxis. The physiological properties of these Ca2+-sensitive mutants were determined. Besides calcium-sensitivity to 75 mM calcium, all of the mutants exhibited increased sensitivities to several divalent cations including Ni2+, Mg2+, Mn2+, Co2+, Zn2+, Cu2+, and Cd2+. To identify the cal gene sequence in the Ca2+-sensitive mutants, the region of the genes fused to the reporter gene (phoA) on the transposon TnphoA was amplified by PCR and sequenced. The sites of the gene fusion for three cal mutants were at the fdoG, gpt and pqi5 genes. The pleiotropic nature for the cal mutations suggested that many genes may be globally regulated by calcium. We then investigated global gene expression patterns of wild-type E. coli under calcium-depleted (addition of 10 mM EGTA) and calcium-elevated (addition of 75 mM Ca2+) conditions as compared to cultures grown under unstressed conditions. A comprehensive transcriptome analysis using macroarrys exhibited a global regulation of diverse genes within the E. coli genome during calcium homeostasis.Bangladesh J Microbiol, Volume 31, Number 1-2,June-Dec 2014, pp 1-8